1998
DOI: 10.1164/ajrccm.158.2.9705007
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-induced Proliferation and Interleukin-5 Production by Bronchoalveolar Lavage and Blood T Cells after Segmental Allergen Challenge

Abstract: In order to detect and characterize allergen-specific T cells in the airways of atopic asthmatics, we measured proliferation and cytokine production by bronchoalveolar lavage (BAL) T cells isolated from Dermatophagoides pteronyssinus (Der p)-sensitive asthmatics and nonatopic control subjects, and compared the results with those generated using peripheral blood (PB) T cells. BAL and PB mononuclear cells were collected 24 h after segmental allergen challenge by fibreoptic bronchoscopy and venepuncture, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 23 publications
4
41
1
Order By: Relevance
“…We previously showed that under these conditions, allergeninduced IL-5 production is detectable in cultures of enriched BAL T cells from atopic asthmatics, but not peripheral blood T cells from the same patients, or BAL T cells from nonatopic normal subjects. Moreover, we reported that allergen-induced IL-5 production by BAL T cells correlated with allergen-induced eosinophilia in the bronchi (28).…”
Section: Bal T Cell Culturesmentioning
confidence: 85%
See 2 more Smart Citations
“…We previously showed that under these conditions, allergeninduced IL-5 production is detectable in cultures of enriched BAL T cells from atopic asthmatics, but not peripheral blood T cells from the same patients, or BAL T cells from nonatopic normal subjects. Moreover, we reported that allergen-induced IL-5 production by BAL T cells correlated with allergen-induced eosinophilia in the bronchi (28).…”
Section: Bal T Cell Culturesmentioning
confidence: 85%
“…We previously reported that IL-5 production by BAL, but not peripheral blood T cells stimulated with allergen and irradiated PBMC (as APC) correlates with the degree of airway eosinophilia and is higher in asthmatics than control subjects (28). Although the APC types in PBMC are unlikely to reflect the exact composition of APC in the lung, a previous report did not find differences in IL-12 responsiveness by allergen-specific peripheralblood T cells stimulated by different APC types (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fiberoptic bronchoscope was introduced into the airway via the oral route, and mucosal biopsy specimens were taken from the carina of the left up-per and lower lobe. Subsequently, SBP was accomplished with a method described previously (16). The tip of the bronchoscope (BF, Type P20 D; Olympus Tokyo, Japan), was wedged in the anterior segment of the right upper lobe (RUL), and 10 ml of 0.9% sterile saline was instilled as a control challenge.…”
Section: Bronchial Biopsies and Segmental Allergen Bronchoprovocationmentioning
confidence: 99%
“…Additionally, IL-5 has been implicated in the development of airway constrictor hyperresponsiveness in various animal models of airway sensitization. Accordingly, recent studies have demonstrated that (a) treatment with IL-5 induces airway constrictor hyperresponsiveness (10)(11)(12); (b) certain strains of genetically IL-5-deficient mice fail to develop airway eosinophilia and constrictor hyperresponsiveness after allergen challenge in the sensitized state (35); and (c) transgenic mice that constitutively overexpress IL-5 exhibit airway inflammatory changes and constrictor hyperresponsiveness, both of which are pathognomonic of human allergic asthma (36). Notwithstanding this evidence, the mechanism(s) by which IL-5 reportedly elicits the proasthmatic phenotype of altered airway responsiveness remains to be identified.…”
mentioning
confidence: 99%